Utilization of Cellulose Symbiotic Culture of Bacteria and Yeast (SCOBY) with Sweet Tea Media as Methylene Blue and Brilliant Green Biosorbent Material - Sigiro, Leonard Mateus; Maksum, Ahmad; Dhaneswara, Donanta (UI Scholars Hub, 2023)
The cellulose from Symbiotic Culture of Bacteria and Yeast (SCOBY) can be used as a biosorbent for dye adsorption, such as Methylene Blue and Brilliant Green. This study used sweet tea with a 6% of sugar concentration and 14 days of fermentation time to synthesize biosorbent material from SCOBY. The results from this synthesis are then characterized using FTIR, SEM, and BET. From the result of characterization, it was found that SCOBY has pores formed from cellulose. The results of the average pore size are 1.5976nm with a pore volume of 0.229cc/g, while the specific surface area is 143.244m2/g. The material that has been characterized is used to absorb the dye using Methylene Blue and Brilliant Green. The mass variation of absorbent is used in this study with variations of 0.5gr, 1gr, and 1.5gr and carried out to absorb the dye for three hours. The highest percentage of dye removal after three hours reached up to 100%, which proved that SCOBY is effective for dye removal.